Contemporary Issues in Geoenvironmental Engineering Proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on Sustainable Civil Infrastructures (Sustainable Civil Infrastructures,, 2018)
With high urbanization rates, advancement in technologies, and changes in consumption behavior of people, wastes generated through the daily activities of individuals and organizations pose many challenges in their management. The articles presented in this edited volume deal with the attempts made by the scientists and practitioners to address contemporary issues in geoenvironmental engineering such as characterization of dredged sediments, geomaterials & waste, valorization of waste, sustainability in waste management and some other geoenvironmental issues that are becoming quite relevant in today's world. This volume is part of the proceedings of the 1st GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2017.